2017
DOI: 10.3174/ajnr.a5123
|View full text |Cite
|
Sign up to set email alerts
|

Site and Rate of Occlusive Disease in Cervicocerebral Arteries: A CT Angiography Study of 2209 Patients with Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE:CTA can rapidly and accurately detect and localize occlusive disease in patients with ischemic stroke. We have used CTA to assess arterial stenosis and occlusion in an ischemic stroke population arriving at a tertiary stroke center within 24 hours of symptom onset in order to obtain a comprehensive picture of occlusive disease pattern, and to determine the proportion of eligible candidates for endovascular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The MT rate of 11.6% is comparable to large observational studies [ 11 ]. The bridging IVT rate of over 60% did not differ between the CT- and MRI-guided group.…”
Section: Discussionsupporting
confidence: 79%
“…The MT rate of 11.6% is comparable to large observational studies [ 11 ]. The bridging IVT rate of over 60% did not differ between the CT- and MRI-guided group.…”
Section: Discussionsupporting
confidence: 79%
“…Meanwhile, most of the intracranial arterial stensis occurs in the trunk of the artery. Of note, previous studies also showed that intracranial arteriostenosis preferably occurs in the midlower segment of the basilar artery, internal carotid siphon, and the trunks before bifurcation in the M1 segment of the middle cerebral artery (22,23). Baek et al demonstrated that the occlusion types (truncaltype occlusion and branching-site occlusion), were independent predictors for ICAS and embolism in intracranial large artery occlusion related AIS (16).…”
Section: Discussionmentioning
confidence: 97%
“…Extracranial or intracranial (i.e. carotid artery to the furthest intracranial segments) occlusion as absent contrast medium filling of the examined arterial segment 12 . Excellent outcome defined as mRS 0–2 at 90-day follow-up.…”
Section: Methodsmentioning
confidence: 99%